Government support measures for outward FDI: an emerging economy’s perspective - Gorynia, Marian; Nowak, Jan; Trąpczyński, Piotr; Wolniak, Radosław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The objective of this paper is to critically review and evaluate the literature related to outward FDI (OFDI) support measures, as well as to propose an approach to classifying them. The review is preceded by a discussion of the positive and negative effects of OFDI on investing firms and home country’s economies and firms, which is an important consideration in decisions related to OFDI support. Subsequently, a typology of various financial and nonfinancial support measures is proposed and applied to the case of Poland as an emerging source of FDI outflows. In this context, current support measures in Poland are identified and a model policy framework is proposed with implications for the overall effectiveness of an OFDI support system
Argumenta Oeconomica, 2015, Nr 1 (34), s. 229-258
Keywords: foreign direct investment; government support; home-country measures; emerging markets